If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -5) + -3(x + -2) = 1 Reorder the terms: 4(-5 + x) + -3(x + -2) = 1 (-5 * 4 + x * 4) + -3(x + -2) = 1 (-20 + 4x) + -3(x + -2) = 1 Reorder the terms: -20 + 4x + -3(-2 + x) = 1 -20 + 4x + (-2 * -3 + x * -3) = 1 -20 + 4x + (6 + -3x) = 1 Reorder the terms: -20 + 6 + 4x + -3x = 1 Combine like terms: -20 + 6 = -14 -14 + 4x + -3x = 1 Combine like terms: 4x + -3x = 1x -14 + 1x = 1 Solving -14 + 1x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 1x = 1 + 14 Combine like terms: -14 + 14 = 0 0 + 1x = 1 + 14 1x = 1 + 14 Combine like terms: 1 + 14 = 15 1x = 15 Divide each side by '1'. x = 15 Simplifying x = 15
| c=180+65h | | (11-7)+g= | | 4-(4-4k)=-10-16 | | 35=w+7 | | 38=-11a-a^2 | | 3/4w=1/5 | | 15=7.5 | | 11v^2-15v+132=10v^2 | | 6(x+-1)=2+8x | | x/1.2=5 | | x+1/2-1=7 | | 3x-15/3=5 | | 48+9(y-7)= | | x/3.7=2.1 | | 3x-7+2x=13 | | 3x/2-3=3 | | 2n^2+12n+36=-7 | | m+(-4.4)=-3.6 | | (3+4x)(5+6x)= | | 4-6x=3x+11 | | 2.1*4.1= | | 0.5x^2+x+0.5=0 | | 3(x-5)+8=-(2-x)-25 | | -2.1x=14 | | p^2+6p-41=0 | | 3x+12=7(2x-3) | | 10x+2x=10x | | 5sinx-4=since | | 2s+4s=2s | | X-1/10=x-9/2 | | w-8.1=6.4 | | 1982.596=2*3.14*8.2*8.2+2*3.14*8.2*h |